Post-embryonic development of mischocyttarus latior (Fox) (Hymenoptera: Vespidae) - Cecílio, D. S.S. [UNESP]; Da Rocha, A. A.; Giannotti, E. [UNESP] (Universidade Estadual de Feira de Santana, 2015)
Mischocyttarus latior (Fox) occurs in Bolivia and Brazil and has been recorded in Cerrado areas from southeast Brazil. The objectives of the present study were to describe the immature stages of M. latior, determine the development time of the immature stages and determine which factors affect its duration. Daily mappings were performed from March 1994 to August 1995 in 22 nests. Two nests were also collected and dissected to characterize immatures. Larvae presented five instars and unlike most Mischocyttarus, M. latior has only a single lobe on the abdominal sternite, which is vestigial in third instar, emergent in fourth instar and fully developed in the fifth instar larvae. The mean duration of the immature stages (from egg laying to adult emergence), was 67.38 ± 9.41 days, a longer period than the total duration of the immature stages of other previously studied species. The development time of the immatures was variable, depending on the colony development stage, with development times being quicker in pre-emergence colonies.
Keywords: Larva; Lobes; Mischocyttarini; Polistinae.